2013
DOI: 10.1002/cphc.201201061
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Cl⋅⋅⋅H and O⋅⋅⋅H Interactions in Self‐Assembled 1,5‐Dichloroanthraquinone Layers on Au(111)

Abstract: The role of halogen bonds in self-assembled networks for systems with Br and I ligands has recently been studied with scanning tunneling microscopy (STM), which provides physical insight at the atomic scale. Here, we study the supramolecular interactions of 1,5-dichloroanthraquinone molecules on Au(111), including Cl ligands, by using STM. Two different molecular structures of chevron and square networks are observed, and their molecular models are proposed. Both molecular structures are stabilized by intermol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…This comparative study illustrated that hydrogen bonding interactions and close packing considerations overrule relatively weak halogen-halogen interactions such as the ClÀ Cl type II contacts. [38] Halogen-halogen type-II contacts have been recently employed to generate exotic supramolecular architectures such as fractals. Fractals are complex patterns that are self-similar across different length scales.…”
Section: Halogen-halogen and Halogen-heteroatoms Interactions At The mentioning
confidence: 99%
“…This comparative study illustrated that hydrogen bonding interactions and close packing considerations overrule relatively weak halogen-halogen interactions such as the ClÀ Cl type II contacts. [38] Halogen-halogen type-II contacts have been recently employed to generate exotic supramolecular architectures such as fractals. Fractals are complex patterns that are self-similar across different length scales.…”
Section: Halogen-halogen and Halogen-heteroatoms Interactions At The mentioning
confidence: 99%
“…Halogen-bonded (XB) molecular nanostructures 1,[7][8][9] are considerably less common in on-surface 2D systems but are increasingly being studied and seen as an important addition to the 'toolbox' of supramolecular assembly. Typically, iodine [10][11][12][13][14] and bromine atoms [15][16][17][18][19] are used as halogen bond donors due to their strong polarisability, but examples of chlorine 20 and fluorine 21,22 based assemblies have also been reported. Halogen bonds can also involve halogen atoms acting simultaneously as both donor and acceptor 11,16,17,23,24 , with the positive electrostatic potential of the sigma hole oriented towards the central 'belt' of negative electrostatic potential found on an adjacent halogen atom.…”
mentioning
confidence: 99%
“…The former can be greater or less than the latter. [15][16][17] In earlier work studying XB and HB between DMSO and three fluorobenzene derivatives(C 6 F 5 H, C 6 F 5 Cl, ClC 6 F 4 H), using both experimental and theoretical approaches, we found that HB was stronger than XB in these binary systemsi fc hlorine was the halogen. [18] Considering that the strength of the bromine-(BrÀXB) and iodine-based halogen bonds (IÀXB) are normally greatert han that of chlorine-based halogen bonds (ClÀXB), we extend our work to these two cases herein.…”
Section: Introductionmentioning
confidence: 91%
“…Noh et al found that both XB and HB could contributep ositively to stabilization of the supramolecular structures. [16] Li et al found that there was significant cooperativity between XB and HB in some complexes. [17] Nevertheless, the electronic structures of the halogen atoms are quite different from that of the hydrogen atom.…”
Section: Introductionmentioning
confidence: 98%